Soil microbiome analysis reveals effects of periodic waterlogging stress on sugarcane growth - Leelastwattanagul, Onnicha; Sutheeworapong, Sawannee; Khoiri, Ahmad Nuruddin; Dulsawat, Sudarat; Wattanachaisaereekul, Songsak; Tachaleat, Anuwat; Duangfoo, Thanawat; Paenkaew, Prasobsook; Prommeenate, Peerada; Cheevadhanarak, Supapon; Jirakkakul, Jiraporn (PloS one, 2023)
Sugarcane is one of the major agricultural crops with high economic importance in Thailand. Periodic waterlogging has a long-term negative effect on sugarcane development, soil properties, and microbial diversity, impacting overall sugarcane production. Yet, the microbial structure in periodically waterlogged sugarcane fields across soil compartments and growth stages in Thailand has not been documented. This study investigated soil and rhizosphere microbial communities in a periodic waterlogged field in comparison with a normal field in a sugarcane plantation in Ratchaburi, Thailand, using 16S rRNA and ITS amplicon sequencing. Alpha diversity analysis revealed comparable values in periodic waterlogged and normal fields across all growth stages, while beta diversity analysis highlighted distinct microbial community profiles in both fields throughout the growth stages. In the periodic waterlogged field, the relative abundance of Chloroflexi, Actinobacteria, and Basidiomycota increased, while Acidobacteria and Ascomycota decreased. Beneficial microbes such as Arthrobacter , Azoarcus , Bacillus , Paenibacillus , Pseudomonas , and Streptomyces thrived in the normal field, potentially serving as biomarkers for favorable soil conditions. Conversely, phytopathogens and growth-inhibiting bacteria were prevalent in the periodic waterlogged field, indicating unfavorable conditions. The co-occurrence network in rhizosphere of the normal field had the highest complexity, implying increased sharing of resources among microorganisms and enhanced soil biological fertility. Altogether, this study demonstrated that the periodic waterlogged field had a long-term negative effect on the soil microbial community which is a key determining factor of sugarcane growth.